2017
DOI: 10.1016/j.hlpt.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Public use of electronic personal health information: Measuring progress of the Healthy People 2020 objectives

Abstract: Use of the internet for seeking and managing health information in the U.S., Europe, and emerging and developing nations is growing. Recent global trends indicate more interactive uses of the internet including online communication with providers. In the U.S., The Healthy People 2020 (HP2020) initiative was created by the Department of Health and Human Services to provide 10-year goals for improving the health of American citizens. Two goals of HP2020 were to increase the proportion of individuals who use the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…At least half of the patients in this study reported using some technologies such as computers, the internet, and the telephone (including text messaging) to manage their health. This finding is consistent with reported trends of individuals' rapidly increasing uptake of technology, such as the internet, to manage their health [19]. However, only a small proportion of patients were interested in using new technologies that they were not currently using in general daily activities in managing their health.…”
Section: Discussionsupporting
confidence: 89%
“…At least half of the patients in this study reported using some technologies such as computers, the internet, and the telephone (including text messaging) to manage their health. This finding is consistent with reported trends of individuals' rapidly increasing uptake of technology, such as the internet, to manage their health [19]. However, only a small proportion of patients were interested in using new technologies that they were not currently using in general daily activities in managing their health.…”
Section: Discussionsupporting
confidence: 89%
“…At least half of the patients in this study reported some technologies such as computers, the internet, and the telephone (including text messaging) to manage their health. This nding is consistent with reported trends of individuals' rapidly increasing uptake of technology, such as the internet, to manage their health (13). However, only a small proportion of patients were interested in using new technologies that they were not currently using in general daily activities in managing their health.…”
Section: Resultssupporting
confidence: 87%
“…Trends through 2014 suggested that people with higher incomes and education remained more likely to use the internet to look up health information and to communicate with their providers, with disparities based on race sometimes becoming statistically nonsignificant in adjusted models [2,8,9]. Throughout this period, group differences in internet and home computer access at least partly explained disparities in eHealth use [5,10].…”
Section: Introductionmentioning
confidence: 99%